Agricultural crops and livestock in the Khawarzum region after the Islamic conquest: (93 AH / 711 AD) - Ahmed, Haleem; Hamid, Wafa (Al-Adab Journal, 2024)
This research focused on an important aspect of economic life in the Khiva region, as the subject of the research centered on the most important agricultural crops in the region, which are the primary source of human and animal food, and provide raw materials for many food and other industries, and what is surplus to requirements is exported abroad, and this is a recovery. For trade, most of the population of the Khwarezm region works in agriculture due to the abundance of rivers and the fertility of the land, in addition to the livestock in the region, as the people of Khwarazm used to acquire all kinds of livestock as it is a source of food, with the abundance of raw materials for various industries such as fur, fur, wool, and others. The Khiva region was distinguished by its agricultural and livestock production, which met local needs and sent much of it to neighboring countries.